2004
DOI: 10.1091/mbc.e03-06-0368
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Regulated Association of Caveolin with Lipid Bodies: Modulation of Lipid Body Motility and Function by a Dominant Negative Mutant

Abstract: Caveolins are a crucial component of caveolae but have also been localized to the Golgi complex, and, under some experimental conditions, to lipid bodies (LBs). The physiological relevance and dynamics of LB association remain unclear. We now show that endogenous caveolin-1 and caveolin-2 redistribute to LBs in lipid loaded A431 and FRT cells. Association with LBs is regulated and reversible; removal of fatty acids causes caveolin to rapidly leave the lipid body. We also show by subcellular fractionation, ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
176
3
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(195 citation statements)
references
References 34 publications
12
176
3
4
Order By: Relevance
“…The actin cytoskeleton, as revealed by phalloidin staining, showed partial colocalization with caveolin-1 in clones 7 and 9 ( Figure 1c). Caveolin-1 did not colocalize with lipid droplets as assessed by Oil Red O staining (data not shown), in contrast to reports in other cell types (Ostermeyer et al, 2001;Pol et al, 2004).…”
contrasting
confidence: 78%
“…The actin cytoskeleton, as revealed by phalloidin staining, showed partial colocalization with caveolin-1 in clones 7 and 9 ( Figure 1c). Caveolin-1 did not colocalize with lipid droplets as assessed by Oil Red O staining (data not shown), in contrast to reports in other cell types (Ostermeyer et al, 2001;Pol et al, 2004).…”
contrasting
confidence: 78%
“…Pol et al 24 reported an important increase and redistribution of Cav-1 from the cell surface to the newly formed lipid bodies in liver regeneration after PH. These authors suggested that this association of Cav-1 with lipid bodies is due to the lipid mobilization process together with the arrest of endocytosis and membrane trafficking that accounts for regenerating liver.…”
Section: Discussionmentioning
confidence: 99%
“…In liver and in different hepatocyte cell lines, the expression of Cav has been demonstrated, 19,20 and the internalization of specific ligands through caveolae has been reported. [21][22][23] Recent reports have identified changes in the expression of Cav-1 in liver regeneration after partial hepatectomy (PH), a process in which Cav-1 seems to be essential, 24,25 in human cirrhotic liver, 26 and in hepatocellular carcinogenesis. 27 In this study, we have investigated the role of Cav-1 in liver regeneration after PH and in liver cell lines.…”
mentioning
confidence: 99%
“…However, this study showed that flotillins were not recruited to lipid bodies, but the authors used a flotillin-2-myc fusion construct to study the targeting of flotillins to lipid droplets, consistent with our finding that flotillin-2 remains unassociated with lipid bodies upon OA treatment. Interestingly, an increasing number of studies have revealed that caveolins can redistribute to lipid droplets under various conditions, including OA treatment (Fujimoto et al, 2001;Ostermeyer et al, 2001;Pol et al, 2001Pol et al, , 2004Brasaemle et al, 2004). This lipid-body targeting of caveolins is thought to regulate cellular lipid balance, especially cellular cholesterol homeostasis Pol et al, 2005;Le Lay et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was recently described that caveolins can move from the plasma membrane to lipid bodies in response to oleic acid treatment (Pol et al, 2001(Pol et al, , 2004. In addition, flotillin-1 has been found in purified lipid droplets formed after fatty acid loading in CHO cells (Liu et al, 2004).…”
Section: Lipid Droplet Association Of Flotillin-1mentioning
confidence: 99%